Beef Handling Practices Among Consumers in the U.S. Virgin Islands - Lillian Nabwiire; Angela M. Shaw; Gail R. Nonnecke; Joey Talbert; Christina Chanes; Terri Boylston; Rodrigo Tarte; Kenneth Prusa (Journal of Food Protection, 2023)
U.S. Virgin Islands (USVI) imports more than 95% of its food. Transportation limitations throughout the territory’s supply chain can make temperature control of protein foods challenging for consumers. This study aimed to characterize the beef handling practices used by consumers in USVI to determine any educational needs. Printed and online surveys (n = 620 total) were disseminated in USVI through extension agents and local media sources. Three hundred and thirty-four consumers completed a 30-question food handling questionnaire on consumption patterns and food handling from purchasing to their kitchen. Frequencies and Pearson chi-square tests of independence were performed. Beef ranked second among the different meat types consumed, 92% of consumers bought beef from grocery stores, and 55% removed beef from shelves immediately after entering the store. When shopping, 59.1% of respondents always checked the use-by/freeze-by dates of beef, 46.3% always separated beef from other foods, but only 27.5% always used insulated bags. Eighty-three percent of consumers returned home within 1 h of shopping, 92% took less than 30 min to store groceries in either a freezer or refrigerator (98%) and during power outages, 45.1% maintained cold temperatures of beef. Seventy-two percent of consumers washed their hands for more than 10 s, but 33% of those from households with a vulnerable person did not use soap to wash their hands and dried them with reusable towels. When cooking, 44.6% of consumers thawed beef within the temperature danger zone, 80.1% did not check the temperature of beef for doneness, and 34 respondents cooked hamburgers below 160°F. Future consumer food safety education initiatives in the USVI should address hand hygiene among food preparers in homes with vulnerable persons, temperature control practices by promoting the use of insulated bags, safe meat thawing techniques, and the use of thermometers during cooking.